Management of GIST - W Wanitsuwan; S Sunpaweravong (Journal of Health Science and Medical Research (JHSMR), 2007)
Gastrointestinal stromal tumor (GIST) is currently defined as a gastrointestinal tract mesenchymal tumor showing positive CD117 (c-kit protein). A GIST is the most common kind of mesenchymal tumor arising from the alimentary tract, and was previously classified as leiomyoma, schwannoma, leiomyoblastoma or leiomyosarcoma. The underlying molecular mechanisms responsible for GIST oncogenesis have been discovered. A mutation occurs in the gene encoding KIT (receptor tyrosine kinase) which stimulates KIT-kinase function that affects over-cell proliferation, and inhibits apoptosis, adhesion, and differentiation into cells in the gut wall and interstitial cells of Cajal (ICCS). The point of mutation status may be a prognostic risk factor for GIST. Surgery is the first-line therapy for patients with a localized primary tumor. However, 40-90% of patients with a primary disease who underwent complete resection had recurrences or the cancer metastasized to other organs after surgery. Targeted therapy with imatinib mesylate has become the standard treatment for recurrence and metastatic GIST. The efficacy of neoadjuvant and adjuvant setting therapy are being explored, which are interesting issues at this time. This review discusses current knowledge of GIST, including epidemiology, clinical presentation, histology, characteristics, diagnosis, and molecular biological and therapeutic aspects of GIST based on current clinical studies.